Nonrelativistic Analysis of Multi-Photon Ionization Using Volkov Solutions - Yadav, Subodh Kumar; Yadav, Kishori; Dhobi, Saddam Husain (Patan Prospective Journal, 2025)
This article investigates the differential cross section (DCS) in laser-assisted hydrogen atom scattering, focusing on the impact of the scattering angle and momentum transfer. By analyzing the DCS trends for different photon interaction scenarios (N=0, N=1, N=2), we uncover the significant influence of external laser fields on scattering dynamics. The DCS decreases with increasing scattering angle, with forward scattering being enhanced and high-angle scattering suppressed. The Volkov wave function is employed to model the quantum state of the particles, providing insights into photon absorption and emission processes. The momentum transfer analysis reveals distinct scattering behaviors: for N=0, the DCS decreases sharply and stabilizes, while for N=1 and N=2, more complex patterns emerge, suggesting the effects of photon absorption and higher-order interactions. These findings enhance our understanding of laser-matter interactions and offer valuable insights for atomic collision physics and quantum control applications.